2019
DOI: 10.1002/mus.26480
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic measurement of the cross‐sectional area of the axillary nerve

Abstract: Introduction The objectives of this study were to determine normal reference values for ultrasonographic measurement of the cross‐sectional area (CSA) of the axillary nerve and to standardize the measurement methods. Methods Sixty healthy volunteers were evaluated. Ultrasonography was performed with the shoulder positioned in 100°–120° abduction and 90° external rotation. The CSA of the axillary nerve was measured bilaterally. Results The normal CSA of the right axillary nerve was 2.9 ± 1.1 mm2. The side‐to‐si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 20 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Five groups (axillary, femoral, long thoracic, saphenous, and suprascapular-supraspinatus fossa) were comprised of just one study. 8,[33][34][35] Fourteen studies reported multiple means at a given anatomical site, such as separate means for males and females, or for right and left sides. 20,[34][35][36][37][38][39][40][41][42][43][44][45][46] The greatest variability in nerve CSA was seen in the brachial plexus, tibial-popliteal fossa, and all three sciatic nerve small groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five groups (axillary, femoral, long thoracic, saphenous, and suprascapular-supraspinatus fossa) were comprised of just one study. 8,[33][34][35] Fourteen studies reported multiple means at a given anatomical site, such as separate means for males and females, or for right and left sides. 20,[34][35][36][37][38][39][40][41][42][43][44][45][46] The greatest variability in nerve CSA was seen in the brachial plexus, tibial-popliteal fossa, and all three sciatic nerve small groups.…”
Section: Resultsmentioning
confidence: 99%
“…8,[33][34][35] Fourteen studies reported multiple means at a given anatomical site, such as separate means for males and females, or for right and left sides. 20,[34][35][36][37][38][39][40][41][42][43][44][45][46] The greatest variability in nerve CSA was seen in the brachial plexus, tibial-popliteal fossa, and all three sciatic nerve small groups. When combining all anatomical locations for individual nerve measurements, the tibial nerve (n = 2916 nerves) was the most assessed, followed by the common fibular nerve (n = 2580 nerves), radial nerve (n = 2326 nerves), sciatic nerve (n = 1470 nerves), sural nerve (n = 1316 nerves), and brachial plexus (n = 1314 nerves).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations